Cortactin Tyrosine Phosphorylation Requires Rac1 Activity and Association with the Cortical Actin Cytoskeleton - Head, Julie A. (The American Society for Cell Biology, 2003)
Cortactin is an F-actin binding protein that activates actin-related protein 2/3 complex and is localized within lamellipodia. Cortactin is a substrate for Src and other protein tyrosine kinases involved in cell motility, where its phosphorylation on tyrosines 421, 466, and 482 in the carboxy terminus is required for cell movement and metastasis. In spite of the importance of cortactin tyrosine phosphorylation in cell motility, little is known regarding the structural, spatial, or signaling requirements regulating cortactin tyrosine phosphorylation. Herein, we report that phosphorylation of cortactin tyrosine residues in the carboxy terminus requires the aminoterminal domain and Rac1-mediated localization to the cell periphery. Phosphorylation-specific antibodies directed against tyrosine 421 and 466 were produced to study the regulation and localization of tyrosine phosphorylated cortactin. Phosphorylation of cortactin tyrosine 421 and 466 was elevated in response to Src, epidermal growth factor receptor and Rac1 activation, and tyrosine 421 phosphorylated cortactin localized with F-actin in lamellipodia and podosomes. Cortactin tyrosine phosphorylation is progressive, with tyrosine 421 phosphorylation required for phosphorylation of tyrosine 466. These results indicate that cortactin tyrosine phosphorylation requires Rac1-induced cortactin targeting to cortical actin networks, where it is tyrosine phosphorylated in hierarchical manner that is closely coordinated with its ability to regulate actin dynamics.